STRATEGI PENANGANAN RESISTENSI SOSIAL SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Lilik Mustofiyah; Nina Mekalungi; Supriyono; Minsih; Ernawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to discover the factors that influence the social resistance of students with special needs in inclusive schools, find useful methods to reduce such social resistance, and study the role of teachers, other students, and parents in supporting social inclusion. Systematic Literature Review (SLR) is the methodology used. The results showed that elements such as stigma, lack of understanding, and limited resources significantly affect social resistance. Inclusive education, individualised approaches, teacher training and parent participation are successful strategies. To create an inclusive and supportive environment, parents, other students and teachers must work together. Inclusive schools give all students, including students with special needs, the opportunity to learn together in the same environment. Challenges faced include social resistance such as harassment, discrimination or exclusion. This social resistance can affect the growth of students with special needs as well as the overall learning environment. Therefore, inclusive education, anti-discrimination policies and support from all relevant parties are essential.This research found that awareness raising, teacher and parent training, and clear policies are the best ways to deal with social resistance. To create a supportive and inclusive school environment, co-operation between teachers, parents and the school community is essential. It is hoped that this research will provide practical suggestions on how to improve social inclusion and make a more equitable learning environment for all students.